A inovação tecnológica em arranjos produtivos locais: a indústria de móveis retilíneos residenciais de Bento Gonçalves (RS) - Sonaglio, Claudia Maria (2006)
The fast changes of the last 20 years, with prominence the ascension of the technologies of information and communication, radically transformed products, processes, uses and people's life. These facts, together with the commercial and financial liberalization promoted a new managerial conformation. It has been understood that the innovations, especially the technological ones, are motors of the competition and of the industrial development. That demands great production flexibility from the companies, to be capable to compete and to stay in this dynamic process. The answer of the companies to the new competitive conformations has been given through innovations of products, processes and organization. However, for these incorporations the companies should possess competences to use the technologies and the available knowledge. On the other hand, the amounts of necessary resources, human and financial, are not always available. This way, the companies have been taken advantage of collaborative strategies to join competences that they still don't possess. The performance in productive arrangements with interactive performances facilitatates the diffusion and generation of innovations, since the local proximity and the common culture allow the transmission and change of knowledge. In this sense, we have searched for an answer, through an exploratory and descriptive method, for the diffusion and the generation of technological innovations in the industry of pieces of residential rectilinear furniture, contemplating the interactions between the companies and the institutions linked to the industry in productive arrangement. It was verified that companies and institutions have been demanding efforts concerning the technological innovation of the industry of pieces of rectilinear furniture residences of Bento Gonçalves (RS). The interactive performance in the environment of the productive arrangement permits a healthy atmosphere for the diffusion and the use of the new knowledge obtained from several sources, especially, through the participation in regional events, and also through national and international research actions and development. The results of this study contributes to detach the importance of the external atmosphere in the diffusion and in the generation of technological innovations, and the recognition of the companies to the advantages associated to the location in the area, to the existent partnerships among the agents and to the innovations adopted in the period.